Mutations in GRK2 cause Jeune syndrome by impairing Hedgehog and canonical Wnt signaling - Michaela Bosakova; Sara P Abraham; Alexandru Nita; Eva Hruba; Marcela Buchtova; S Paige Taylor; Ivan Duran; Jorge Martin; Katerina Svozilova; Tomas Barta; Miroslav Varecha; Lukas Balek; et al. (EMBO Molecular Medicine)
Abstract Mutations in genes affecting primary cilia cause ciliopathies, a diverse group of disorders often affecting skeletal development. This includes Jeune syndrome or asphyxiating thoracic dystrophy (ATD), an autosomal recessive skeletal disorder. Unraveling the responsible molecular pathology helps illuminate mechanisms responsible for functional primary cilia. We identified two families with ATD caused by loss‐of‐function mutations in the gene encoding adrenergic receptor kinase 1 (ADRBK1 or GRK2). GRK2 cells from an affected individual homozygous for the p.R158* mutation resulted in loss of GRK2, and disrupted chondrocyte growth and differentiation in the cartilage growth plate. GRK2 null cells displayed normal cilia morphology, yet loss of GRK2 compromised cilia‐based signaling of Hedgehog (Hh) pathway. Canonical Wnt signaling was also impaired, manifested as a failure to respond to Wnt ligand due to impaired phosphorylation of the Wnt co‐receptor LRP6. We have identified GRK2 as an essential regulator of skeletogenesis and demonstrate how both Hh and Wnt signaling mechanistically contribute to skeletal ciliopathies.